Expert workshop summary: Advancing toward a standardized murine model to evaluate treatments for antimicrobial resistance lung infections - Arrazuria, Rakel; Kerscher, Bernhard; Huber, Karen E.; Hoover, Jennifer L.; Lundberg, Carina Vingsbo; Hansen, Jon Ulf; Sordello, Sylvie; Renard, Stephane; Aranzana-Climent, Vincent; Hughes, Diarmaid; Gribbon, Philip; Friberg, Lena E.; et al. (Frontiers in Microbiology, 2022)
Abstract The rise in antimicrobial resistance (AMR), and increase in treatment-refractory AMR infections, generates an urgent need to accelerate the discovery and development of novel anti-infectives. Preclinical animal models play a crucial role in assessing the efficacy of novel drugs, informing human dosing regimens and progressing drug candidates into the clinic. The Innovative Medicines Initiative-funded “Collaboration for prevention and treatment of MDR bacterial infections” (COMBINE) consortium is establishing a validated and globally harmonized preclinical model to increase reproducibility and more reliably translate results from animals to humans. Towards this goal, in April 2021, COMBINE organized the expert workshop “Advancing towards a standardized murine model to evaluate treatments for AMR lung infections”. This workshop explored the conduct and interpretation of mouse infection models, with presentations on PK/PD and efficacy studies of small molecule antibiotics, combination treatments (β-lactam / β-lactamase inhibitor), bacteriophage therapy, monoclonal antibodies and iron sequestering molecules, with a focus on the major Gram-negative AMR respiratory pathogens Pseudomonas aeruginosa, Klebsiella pneumoniae and Acinetobacter baumannii. Here we summarize the factors of variability that we identified in murine lung infection models used for antimicrobial efficacy testing, as well as the workshop presentations, panel discussions and the survey results for the harmonization of key experimental parameters. The resulting recommendations for standard design parameters are presented in this document and will provide the basis for the development of a harmonized and bench-marked efficacy studies in preclinical murine pneumonia model.